Synthesis, Biological Evaluation, X-Ray Structure, and Pharmacokinetics of Aminopyrimidine c-jun-N-terminal Kinase (JNK) Inhibitors - Kamenecka, Ted (2010)
Given the significant body of data supporting an essential role for c-jun-N-terminal kinase (JNK) in neurodegenerative disorders, we set out to develop highly selective JNK inhibitors, with good cell potency, and good brain penetration properties. The structure activity relationships (SAR) around a series of aminopyrimidines was evaluated utilizing biochemical and cell- based assays to measure JNK inhibition, and brain penetration in mice. Microsomal stability in three species, P450 inhibition, inhibition of generation of reactive oxygen species (ROS), and pharmacokinetics in rats were also measured. Compounds 9g, 9i, 9j, and 9l had greater than 135-fold selectivity over p38, and cell-based IC(50) values < 100 nM. Moreover, compound 9l showed an IC(50)= 0.8 nM for inhibition of ROS and had good pharmacokinetic properties in rat, along with a brain-to-plasma ratio of 0.75. These results suggest that biaryl substituted aminopyrimidines represented by compound 9l may serve as the first small molecule inhibitors to test efficacy of JNK inhibitors in neurodegenerative disorders.